The Wiley-Blackwell handbook of the psychology of leadership, change and organizational development - Leonard, H. Skipton (Hoboken, N.J. : Wiley-Blackwell, 2013)
A state-of-the-art reference, drawing on key contemporary research to provide an in-depth, international, and competencies-based approach to the psychology of leadership, change and OD Puts cutting-edge evidence at the fingertips of organizational psychology practitioners who need it most, but who do not always have the time or resources to keep up with scholarly researchThematic chapters cover leadership and employee well-being, organizational creativity and innovation, positive psychology and Appreciative Inquiry, and leadership-culture fitContributors include.
About the editors -- About the contributors -- Foreword -- The role of psychology in OD, change and leadership / Skip Leonard, Rachel Lewis, Arthur Freedman and Jonathan Passmore -- Leadership -- A critical review of leadership theory / Beverly Alimo-Metcalfe -- Evidence-based management and leadership / Rob B. Briner and Neil D. Walshe -- Psychodynamic issues in organizational leadership / Manfred F.R. Kets de Vries, Elizabeth Florent-Treacy and Konstantin Korotov -- Do i trust you to lead the way? exploring trust and mistrust in leader-follower relations / Michelle C. Bligh & Jeffrey C. Kohles -- Leader-culture fit : aligning leadership and corporate culture / Gary N. Burns, Lindsey Kotrba, and Daniel Denison -- When leaders are bullies : concepts, antecedents and consequences / Staale Einarsen, Anders Skogstad & Lars Glas? -- Leadership and employee wellbeing / Emma Donaldson-Feilder, Fehmidah Munir and Rachel Lewis -- Transformational leadership and psychological well-being : effects on followers and leaders / Kara A. Arnold and Catherine E. Connelly -- The potential role of mindfulness in leadership / Michael Chaskalson & Jeremy Hunter -- The future of leadership / David V. Day and John Antonakis -- Change -- The history and current status of organizational and systems change theory / H. Skipton Leonard -- Positive psychology and appreciative inquiry : the contribution of the literature to an understanding of the nature and process of change in organisations / Stefan P. Cantore and David L. Cooperrider -- Participation and organizational commitment during change : from utopist to realist perspectives / Rune Lines and Marcus Selart -- Development approaches for enhancing organisational creativity and innovation / Jane Henry -- Individual readiness for organizational change / Myungweon Choi and Wendy E.A. Ruona -- Toward an integration of stage theories of planned organizational change / Janice M. Prochaska, James O. Prochaska, and Dustin Bailey -- Culture and change in developing western countries / Anthony Montgomery -- Organization development -- A critical review of organization development / Bernard Burnes -- The application of systems theory to organizational diagnosis / Arthur M. Freedman -- Od research interventions : perspectives from action research and collaborative management research / David Coghlan and A.B. (Rami) Shani -- Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: Leadership -- Psychological aspects; Organizational change; Leadership -- Psychological aspects; Organizational change; Leadership -- Psychological aspects; Organizational change; Electronic books